Review of Reviews (Umbrella Reviews): Step-by-Step Guide - Donato, Helena (2024)
In recent years, as a result of the dramatic increase in the number of systematic reviews, a new type of systematic review, the ‘systematic reviews of systematic reviews’, also known as umbrella reviews, reviews of reviews, meta-reviews or synthesis of review, was developed. The aim of this article is to provide recommendations on how this type of systematic review should be conducted and reported to ensure its quality and usefulness. These reviews are designed to compile evidence from multiple systematic reviews of interventions into an accessible and usable document and are one of the highest levels of evidence synthesis.